2023
DOI: 10.15421/012308
|View full text |Cite
|
Sign up to set email alerts
|

Features of the seasonal dynamics of airborne fungal spore concentrations in Ukraine

Abstract: Fungi represent a distinct kingdom of ubiquitous living beings. Most other organisms are constantly in contact with elements of the fungal body. In particular, the widespread vegetation of fungi in the environment, their sporulation and the further spread of spores and mycelia by air currents make the contact of fungal particles with human respiratory organs inevitable. This can lead to the development of sensitization and allergies. Therefore, the aim of the presented study was to determine the taxonomy of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Long-term aerobiological monitoring in Europe and worldwide has shown that fungi of the genus Alternaria are widespread. According to reports from two air monitoring stations in Vinnytsia [1] and Zaporizhzhya [2], the fungus Alternaria is predominant in the air of Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term aerobiological monitoring in Europe and worldwide has shown that fungi of the genus Alternaria are widespread. According to reports from two air monitoring stations in Vinnytsia [1] and Zaporizhzhya [2], the fungus Alternaria is predominant in the air of Ukraine.…”
Section: Introductionmentioning
confidence: 99%